Three Lectures on Monetary Theory and Policy: Speaking Notes and Background Papers - David Laidler (Oesterreichische Nationalbank (OeNB), 2006)
In order to promote the exchange of ideas and to support its own research capacity, the Oesterreichische Nationalbank regularly invites internationally renowned economists for short guest professorships. This year, from June 12 -14 2006, David Laidler gave three public lectures on topics related to monetary theory and monetary policy. The first lecture was on "Monetary Policy and the Austrians", the second on "The Rise and Fall of Monetarism" and the third has dealt with the question "Is there a Role for Money in Monetary Policy in the 21st Century?". The lectures were based on three background papers, which are contained in this OeNB Working Paper that also includes the lecture notes that were prepared for the lecture series.
Keywords: 330